Clinico-pathological analysis of lymphoproliferative disorders: a 3 year study - Varma, K. Rajasree; T., Farzana; Thomas, Sunitha; Abraham, Latha K. (International Journal of Research in Medical Sciences, 2020)
Background: The incidence of lymphoproliferative disorders has increased in many parts of the world. Newer subtypes have been identified by the new WHO classification. Accurate subtyping of lymphomas is crucial for prompt treatment. Objective of the study was to assess the clinicopathological pattern of lymphoproliferative diseases diagnosed in Rajagiri hospital over a period of 3 years. Methods: A retrospective study on all patients who were diagnosed with lymphoma in Rajagiri hospital during January 2016 to December 2018 was conducted and the data were reviewed and analyzed. Results: A total of 151 patients were included in the study. Majority of the subjects (63%) were males. The predominant age group affected was 61-80 years. Mean age group was 58.46 years (SD=19.05 years). Most common presenting symptom was painless lymphadenopathy. B symptoms were seen in 18% of subjects and was found to be more commonly associated with B cell Non-Hodgkin lymphoma. Most common lymph node involved was cervical lymph node, while the most common extra nodal site was bone marrow. Most common lymphoproliferative disorder was Diffuse large B cell Lymphoma. Lymph node involvement was found in 74% of patients, while hepatomegaly and splenomegaly were seen in 11% and 18.5% of patients. 20% of patients had secondary bone marrow involvement. 8 patients developed recurrent lesions involving other organs. Conclusions: Clinicopathologic patterns of lymphoproliferative disorders vary across various regions. A proper understanding of demographical distribution of lymphomas is very essential, as it can provide valuable clues for accurate diagnosis and treatment.